2016
DOI: 10.1248/bpb.b16-00249
|View full text |Cite
|
Sign up to set email alerts
|

Inter-laboratory Variability of Current Immunoassay Methods for Tacrolimus among Japanese Hospitals

Abstract: The aim of this study was to assess inter-hospital laboratory variability (coefficient of variation; CV) of immunoassay methods for tacrolimus and the comparability of control samples and results obtained by immunoassay measurements. One hundred seven hospital laboratories routinely performing therapeutic drug monitoring (TDM) of tacrolimus participated in the study. Thirteen spiked samples with known tacrolimus concentrations in the range of 0-26.0 ng/mL were prepared. Each spiked sample was analyzed accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…CLIA systematically yielded a higher CyA concentration than UPLC-TMS did (15). Compared to EMIT, CLIA and ECLIA have a higher sensitivity and a higher precision when measuring the tacrolimus concentration in blood (16). However, no study has compared EMIT and CLIA or ECLIA when measuring the CyA concentration as part of TDM, so this topic should be studied further.…”
Section: Discussionmentioning
confidence: 99%
“…CLIA systematically yielded a higher CyA concentration than UPLC-TMS did (15). Compared to EMIT, CLIA and ECLIA have a higher sensitivity and a higher precision when measuring the tacrolimus concentration in blood (16). However, no study has compared EMIT and CLIA or ECLIA when measuring the CyA concentration as part of TDM, so this topic should be studied further.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation of albumin with the interassay differences may possibly be explained by the presence of unbound Tac or metabolites with a lower affinity for albumin, still able to cross-react with the antibody [39]. Some studies found that immunoassays appear unable to analyze Tac concentrations in the lower concentration range (between 3.0 and 5.0 ng/mL) and have a higher coefficient of variation (CV) [40]. Tac concentration measurement by LC-MS methods have higher sensitivity, precision, and accuracy, while the application of LC-MS in individual centers is limited.…”
Section: Analytical Issuesmentioning
confidence: 99%
“…Schniedewind et al 77 Miura et al 84 The magnitude of the bias varied considerably. Monitoring free MPA creates additional challenges because free MPA approximated by the fraction of total MPA concentration may be misleading in many conditions such as uremia, hypoalbuminemia, and hepatic dysfunction.…”
Section: New Immunoassay Methodsmentioning
confidence: 99%
“…Miura et al assessed the inter‐hospital laboratory variability of immunoassay methods for TAC. The results were obtained by immunoassay including an affinity column‐mediated immunoassay (ACMIA) on a Dimension analyzer, an enzyme‐multiplied immunoassay technique (EMIT) on a Viva‐E analyzer, a CLIA on the Architect system, and the ECLIA on a cobas analyzer.…”
Section: Immunoassaysmentioning
confidence: 99%